Intravenous alteplase has different effects on the efficacy of aspiration and stent retriever thrombectomy: analysis of the COMPASS trial. (14th October 2021) - Mokin, Maxim; Waqas, Muhammad; Fifi, Johanna T; De Leacy, Reade; Fiorella, David; Levy, Elad I; Snyder, Kenneth; Hanel, Ricardo A; Woodward, Keith; Chaudry, Imran; Rai, Ansaar T; Frei, Donald; et al.
Abstract : Background: There is conflicting evidence on the utility of intravenous (IV) alteplase in patients with emergent large vessel occlusion (ELVO) treated with mechanical thrombectomy (MT). Methods: This was a post hoc analysis of the COMPASS: a trial of aspiration thrombectomy versus stent retriever thrombectomy as first-line approach for large vessel occlusion. We compared clinical, procedural and angiographic outcomes of patients with and without prior IV alteplase administration. Results: In the COMPASS trial, 235 patients had presented to the hospital within the first 4 hours of stroke symptom onset and were eligible for analysis. On univariate analysis, administration of IV alteplase prior to MT was found to be significantly associated with favorable outcomes (modified Rankin scale (mRS) 0–2 at 3 months; 55.6% vs 40.0% in the MT-only group, P=0.037). However, on multivariate analysis, only baseline (pre-stroke) mRS, admission National Institutes of Health Stroke Scale (NIHSS) score and age were identified as independent predictors of favorable outcomes at 3 months. We found higher final thrombolysis in cerebral infarction (TICI) 2b/3 rates in patients without the use of alteplase prior to the aspiration first approach (100.0% vs 87.9% in IV altepase +aspiration first MT, P=0.03). In the stent retriever first group, final TICI 2b/3 rates were identical in patients with and without IV alteplase administration (87.5% and 87.5%, P=1.0). Conclusions: Prior administration of IV alteplase may adversely affect the efficacy of aspiration, but does not seem to influence the stent retriever first approach to MT in patients with anterior circulation ELVO.